Pemerolehan bahasa anak berkebutuhan khusus (tunarungu) dalam memahami bahasa - Nur Haliza; Eko Kuntarto; Ade Kusmana (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2020)
Children with hearing impairment are children with hearing loss who are classified into deaf and hard of hearing. The direct impact of disability is the obstruction of verbal / verbal communication, both speaking (expressive) and understanding the conversations of others (receptive). Obtaining the first language of a deaf child can be done with total communication. Total communication is the most effective communication system because in addition to using a form of communication orally or called oral, the activity of reading, writing, reading utterances, is also equipped with a form of cues. The purpose of this study was to determine the acquisition of language of children with special needs (deaf) in understanding language. Subjects in this study are children with special needs who experience speech impairment (hearing impairment) while the object of this study is focused on only one child, Mila Erdita, a 15-year-old child. This research refers to case studies with descriptive research type. Data collection techniques in this study will be done in three ways, namely; observation techniques, interview techniques, and documentation techniques. In this research, data processing that will be done is to describe the speech data of deaf children to see the acquisition of children's vocabulary. The results of this study indicate that deaf children can obtain a language of total communication using a form of communication orally or called oral, with the activities of reading, writing, reading utterances, also equipped with signs